Blind spot: when journalists don't get religion - Marshall, Paul A.; Gilbert, Lela; Green, Roberta (Oxford University Press, 2009)
Today understanding of religion is essential to understanding many major news stories. This text examines how the media frequently miss or misunderstand these stories because they do not take religion seriously, and how they misunderstand religion when they do take it seriously.